Pengaruh Profitabilitas, Rasio Resiko Bank, dan Kualitas Aktiva Produktif Terhadap Kepercayaan Investor - Vidya Putri, Hasanah; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 28 No 3 (2019)DO - 10.24843/EJA.2019.v28.i03.p25, 2019)
This study aims to determine the factors that influence investor confidence in Islamic banking. The data used in this study were obtained from the financial statements of sharia banking companies published in 2015-2017 with a population of 36 Islamic banking companies. This study hypothesizes profitability, bank risk ratios, and the quality of earning assets as independent variables and investor trust as the dependent variable. This research is located on the Indonesia Stock Exchange (IDX). The sampling method uses a purposive sampling technique. The research data was obtained through non-participant observation methods with secondary data retrieval. Analysis of research data using multiple linear regression with the SPSS application. The results of this study indicate that profitability has a positive effect on investor confidence, the bank's risk ratio has a negative effect on investor confidence and the quality of earning assets has a positive effect on Investor Trust. Simultaneously all independent variables have a significant effect on the dependent variable. Keywords : Profitability ratio, bank risk ratio, productive asset quality, investor trust.